Developing Costed Menus of Nutrition-Sensitive Actions in Relation to the Agri-Food System in Bangladesh - Mahmood, Shehrin; Rasheed, Sabrina; Ahmed, Mohammad Wahid; Islam Tisha, Khadija; Rahman Sakin, Zillur; Nasrin, Towhida; Hasan, A M Rumayan; Mizan, Arefin; Roy, Prantik (WorldFish, 2024)
This report underscores the critical role of nutrition-sensitive interventions in tackling malnutrition and food insecurity in Bangladesh. It seeks to systematically identify key interventions suitable for scaling up, assess the current landscape of such nutrition-sensitive interventions, evaluate their effectiveness through a review of existing literature, and conduct cost analyses of selected interventions to develop comprehensive guidelines for their implementation.